APLIKASI ARSIP SURAT BERBASIS WEBSITE MENGGUNAKAN XAMPP PHP MYSQL: STUDY KASUS: RA IZHHAARUL-HAQ - Ayu Nuraini; Fadzar Rusghana (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Technological developments are currently increasingly advanced so that they have an impact on the use of technology and make it easier in all process activities carried out. Technological developments are needed by the community to overcome the problems they face, such as filing letters or documents in an institution, one of which is at school. Mail management that uses manual storage often results in errors in data storage and mail search. The purpose of making this mail archive application is to assist agencies in managing mail archive data so that it is easier to implement, one of which is changing the way letters are stored by reducing paper use. This application is made using the visual studio code application, while the programming language uses PHP, MySQL as database managers. The system development method used is waterfall. The result of this research is to produce a system that can manage incoming and outgoing mail which has succeeded in increasing the effectiveness and efficiency of mail filing in schools. Using this application reduces the time needed to search and archive mail and improves management of mail archives.